Between Self-Regulation and Participatory Monitoring: Comparing Digital News Media Accountability Practices in Spain - Pérez-Díaz, Pedro-Luis (2020)
In recent years, the accountability practices of digital journalism have gone from constituting an intimate and self-regulatory system of journalistic culture to a complex process that is increasingly external and open to the public (Fengler, Eberwein, Mazzoleni, Porlezza, & Russ-Mohl, 2014; Suárez-Villegas, Rodríguez-Martínez, Mauri-Ríos, & López-Meri, 2017). In this context, values and goals may remain diverse, arguably linked to idiosyncratic elements which often open a gap between traditional and more contemporary newsroom models. Following a qualitative approach, this study examines online media accountability instruments from a functional perspective, dividing its influence in three temporal phases of news production (Heikkilä et al., 2012). In this way, instruments that hold journalists responsible for their work are explored in four leading online news media from Spain: two digital native outlets (Eldiario.es and ElConfidencial.com) and two legacy outlets (ElPais.com and ElMundo.es). In addition to this observation, in-depth interviews are conducted with staff members in charge of audience management to explore the inner routines and protocols that determine the efficacy of such aspirations. Our work reveals the preponderant role of instruments focused on the actor and production transparency that the studied media implement to fulfill their responsibility, especially when compared with the weakened self-regulation instruments. The answers of the interviewees stress the difficulties they face in managing participatory forms of accountability and disclose tensions between different strategies, as well as other structural factors that are discussed as essential for the consolidation of these deontological initiatives.